High-Throughput Sequencing and Metabolomics Reveal Differences in Bacterial Diversity and Metabolites Between Red and White Sufu - Tan, Guiliang; Hu, Min; Li, Xueyan; Pan, Ziqiang; Li, Mei; Li, Lin; Yang, Maoxun (Frontiers in Microbiology, 2020)
Sufu is a traditional fermented soybean food produced in China. However, the microbial compositions and metabolites of different types of sufu have not been studied in detail. Accordingly, in this study, we evaluated the differences in bacterial communities and metabolites between commercial red sufu (RS) and white sufu (WS). Principal coordinate analysis and the unweighted pair group method with arithmetic means analysis of 16S rRNA genes revealed that the bacterial community structures of RS and WS differed dramatically. At the phylum level, the relative abundances of Firmicutes and Proteobacteria were significantly different between RS and WS (P < 0.01). Moreover, the abundances of Lactococcus and Tetragenococcus genera were significantly different between RS and WS (P < 0.01). Among metabolites, most free amino acids, few of volatile flavor compounds, and some organic acids showed significant differences between RS and WS (P < 0.05). Additionally, correlations between microbiota and metabolites were determined. Aggregated boosted tree analysis showed that formic acid had the highest relative influence (20.27%) on bacterial community diversity (Chao 1), following by arginine (5.38%), propanol (4.57%), oxalic acid (4.46%), and hexanol (4.43%). Moreover, Streptococcaceae and Moraxellaceae had the highest relative influence on the concentration of formic acid (12.84% and 8.75%, respectively). The profiles obtained in this study improve our understanding of the relationships between bacterial flora and metabolites in different types of sufu. These findings may help us interpret the roles of bacterial communities in the flavor and characteristics of sufu.